2010
DOI: 10.1007/s10557-010-6234-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and GSK-3β in Cardioprotection Against Ischemia/Reperfusion Injury

Abstract: The mitochondrion is a powerhouse of the cell, a platform of cell signaling and decision-maker of cell death, including death by ischemia/reperfusion. Ischemia shuts off ATP production by mitochondria, and cell viability is compromised by energy deficiency and build-up of cytotoxic metabolites during ischemia. Furthermore, the mitochondrial permeability transition pore (mPTP) is primed by ischemia to open upon reperfusion, leading to reperfusion-induced cell necrosis. mPTP opening can be suppressed by ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 111 publications
(185 reference statements)
5
56
0
Order By: Relevance
“…This may contribute to higher susceptibility to mPTP opening (Marzetti et al., 2008) and to the reduction in affinity of ANT for CypD. An increased phospho‐GSK‐3β binding to ANT was suggested to be responsible for the inhibition of mPTP opening (Miura & Tanno, 2010; Nishihara et al., 2007). This mechanism would contribute to the cardioprotective effect of several drugs such as formononetin or resveratrol and of ischemic preconditioning (Cheng, Xia, Han, & Rong, 2016; Xi, Wang, Mueller, Norfleet, & Xu, 2009; Zhu, Rebecchi, Glass, Brink, & Liu, 2013; Zhu, Rebecchi, Wang, et al., 2013).…”
Section: Putative Molecular Components Of Mptp and Agingmentioning
confidence: 99%
“…This may contribute to higher susceptibility to mPTP opening (Marzetti et al., 2008) and to the reduction in affinity of ANT for CypD. An increased phospho‐GSK‐3β binding to ANT was suggested to be responsible for the inhibition of mPTP opening (Miura & Tanno, 2010; Nishihara et al., 2007). This mechanism would contribute to the cardioprotective effect of several drugs such as formononetin or resveratrol and of ischemic preconditioning (Cheng, Xia, Han, & Rong, 2016; Xi, Wang, Mueller, Norfleet, & Xu, 2009; Zhu, Rebecchi, Glass, Brink, & Liu, 2013; Zhu, Rebecchi, Wang, et al., 2013).…”
Section: Putative Molecular Components Of Mptp and Agingmentioning
confidence: 99%
“…The phosphorylation of p53 by GSK-3β is essential for its acetylation and subsequent translocation into mitochondria [67]. It has been demonstrated that p53-regulated mPTP opening can be abrogated by GSK-3β inhibition [68]. …”
Section: Gsk-3β Regulates Mitochondrial Permeabilitymentioning
confidence: 99%
“…MPT induction can be suppressed by IPC and other interventions that increase phosphoSer 9 -GSK-3β [3,23,[40][41][42][43]. GSK-3β is an important regulator of cell function, controlling gene expression, cell cycle, survival, and apoptosis [44][45][46]. Upon reperfusion, phospho-Ser 9 -GSK-3β in mitochondria physically interacts with the adenine nucleotide translocator (ANT) and the voltage-dependent anion channel (VDAC), thus impairing the interaction of the ANT with cyclophilin D (CypD), elevating the threshold for MPT induction [40,42,46,47].…”
Section: Introductionmentioning
confidence: 99%